Diseñar una planta de tratamiento de gas, mediante el software Aspen Hysis para el aprovechamiento del gas producido en Campo Tello (2020)
The Tello field located in the Upper Valley basin and which is operated and developed by Ecopetrol handled the gas as a fluid associated with the production of low-interest wells that thanks to its composition make it unfeasible for the supply of combustion engines, since by itself it contains a low Methane Number and a high content of heavy hydrocarbons. In this order of ideas and since then, the gas has been burning in the air, with the respective payment of royalties according to the resolutions given by the ANH. On the other hand, the Tello field has an Electric Generation Contract that receives the gas from other sources that meet the gas conditions, however; This resource has been reduced and energy demand is met by buying from the National Interconnected (Electric) System. For this, he designed a gas treatment plant in order to take advantage of this asset produced in Tello Field for power generation and thus reduce the costs of operating the field and the company in specific.